Best Answer

Divide by 9 to make the conversion. This works out to 6 square yards.

More answers

54 square feet = 6 square yards.

Q: How many sq yd in 54 sq ft?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3 ft x 3 ft = 9 sq ft or 1 sq yd 6 sq yds x 9 sq ft / sq yd = 54 sq ft

9 sq ft = 1 sq yd525 sq ft = 581/3 sq yd

1 sq yd = 9 sq ft61.33 sq yd = (61.33 x 9) = 551.97 sq ft

1 yd = 3 ft 1 sq yd = 1 yd x 1 yd = 3 ft x 3 ft = 9 sq ft ⇒ 70 sq yds = 70 x 9 sq ft = 630 sq ft

1 sq. yd. = 9 sq. ft. 1000 / 9 sq. yd. = 1000 sq. ft. = about 111 sq. yd.

Related questions

3 ft x 3 ft = 9 sq ft or 1 sq yd 6 sq yds x 9 sq ft / sq yd = 54 sq ft

1 sq yd are in 9 sq ft

9 sq ft = 1 sq yd525 sq ft = 581/3 sq yd

3 ft/yd x 3 ft/yd = 9 sq ft/ sq yd.

1 sq yd = 1 yd*1 yd = 3 ft * 3 ft = 9 sq ft So 1000 sq ft = 1000/9 = 111. 11... sq yds.

1 sq yd = 9 sq ft61.33 sq yd = (61.33 x 9) = 551.97 sq ft

1 sq yd = 1 yd * 1 yd = 3 ft * 3 ft = 9 sq ft. 11 ft * 9 ft = 11*9 sq ft = 99 sq ft = 99/9 sq yd = 11 sq yd

1 yd = 3 ft 1 sq yd = 1 yd x 1 yd = 3 ft x 3 ft = 9 sq ft ⇒ 1 sq ft = 1/9 sq yd ≈ 0.11 sq yd

1 yd = 3 ft 1 sq yd = 1 yd x 1 yd = 3 ft x 3 ft = 9 sq ft ⇒ 70 sq yds = 70 x 9 sq ft = 630 sq ft

1 sq. yd. = 9 sq. ft. 1000 / 9 sq. yd. = 1000 sq. ft. = about 111 sq. yd.

1 yd = 3 ft 1 sq yd = 1 yd x 1 yd = 3 ft x 3 ft = 9 sq ft ⇒ 375 sq yd = 375 x 9 sq ft = 3375 sq ft

first ,let us find the relation between 1 yd sq and 1 ft sq .we get the relation as :1 ft sq= 0 yd sq 1.000 ft sqconverting now ,132 ft sq =14 yd sq 6.00000 ft sq